UPAYA PENINGKATAN PEMBELAJARAN PERMAINAN BOLA BASKET MELALUI METODE PENDEKATAN TAKTIK PADA SISWA KELAS VIII C SMP NEGERI 2 PANDAK BANTUL - Yudha Febrianta (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
This study aims to improve basketball learning through the tactics approach method among Grade VIII C students of SMP Negeri 2 Pandak Bantul. This was a classroom action research (CAR) study consisting two cycles. The research subjects were 36 Grade VIII C students of SMP Negeri 2 Pandak, Bantul. The data were collected through: (1) observations on the basketball learning outcomes using the tactics approach method, (2) classroom observations on the teacher, (3) observations on classroom situations, (4) observations on students’ behaviors, and (5) a cognitive test. The results of the study revealed that there was an improvement in basketball learning through the tactics approach method among Grade VIII C students of SMP Negeri 2 Pandak, Bantul. Basketball learning through the tactics approach method among Grade VIII C in 2 cycles improved the process skills in playing basketball game with the tactics approach. Based on the assessment at the end of Cycle I, the students’ average score was 72.8. At the end of Cycle II, their average score improved to 78.0, so it was above the Minimum Mastery Criterion (MMC), i.e. 71. Meanwhile, the number of students who attained MMC in Cycle I was 17 (47%), and in Cycle II it became 33 (96%); this was above the class mastery, i.e. 75%. The class mastery from the cognitive aspect could be explained as follows: from the pretest results, the mastery was 16.67%, in Cycle I it was 91.67%, and in Cycle II it was 100%. The recapitulation from the observations on the students’ learning behaviors in Cycle I was 2.8, improving to 3.8 in Cycle II; that from the observations of teachers in Cycle I was 2.9, improving to 3.7 in Cycle II; and the class situation in Cycle I was 2.7, improving to 3.7 in Cycle II